Targeted neurotechnology restores walking in humans with spinal cord injury. (1st November 2018) - Wagner, Fabien; Mignardot, Jean-Baptiste; Le Goff-Mignardot, Camille; Demesmaeker, Robin; Komi, Salif; Capogrosso, Marco; Rowald, Andreas; Seáñez, Ismael; Caban, Miroslav; Pirondini, Elvira; Vat, Molywan; McCracken, Laura; et al.
Abstract Spinal cord injury leads to severe locomotor deficits or even complete leg paralysis. Here we introduce targeted spinal cord stimulation neurotechnologies that enabled voluntary control of walking in individuals who had sustained a spinal cord injury more than four years ago and presented with permanent motor deficits or complete paralysis despite extensive rehabilitation. Using an implanted pulse generator with real-time triggering capabilities, we delivered trains of spatially selective stimulation to the lumbosacral spinal cord with timing that coincided with the intended movement. Within one week, this spatiotemporal stimulation had re-established adaptive control of paralysed muscles during overground walking. Locomotor performance improved during rehabilitation. After a few months, participants regained voluntary control over previously paralysed muscles without stimulation and could walk or cycle in ecological settings during spatiotemporal stimulation. These results establish a technological framework for improving neurological recovery and supporting the activities of daily living after spinal cord injury. Spatially selective and temporally controlled stimulation of the spinal cord, together with rehabilitation, results in substantial restoration of locomotor function in humans with spinal cord injury.